Historical Archaeology - Funari, Pedro Paulo A.
1 online resource (371 pages)
Keywords: Historical Archaeology demonstrates the potential of adopting a flexible, encompassing definition of historical archaeology which involves the study of all societies with documentary evidence. It encourages research that goes beyond the boundaries between prehistory and history. Ranging in subject matter from Roman Britain and Classical Greece, to colonial Africa, Brazil and the United States, the contributors present a much broader range of perspectives than is currently the trend.